2017
DOI: 10.1007/s10006-017-0621-6
|View full text |Cite
|
Sign up to set email alerts
|

Brief alcohol intervention in alcohol involved facial fracture patients—a survey of patient attitudes to screening and intervention

Abstract: Most patients presented in this survey were in moderate risk category who are amenable to behavioural change with provision of SBI. However, there is resistance to implementation of this intervention due to lack of knowledge, self-awareness and willingness to change. Nonetheless, patients are prepared to accept advice from clinicians and some formats of intervention. It is important to formulate a simple screening questionnaire and intervention strategy that are easy to administer to affect positive changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
2
1
0
Order By: Relevance
“…In these published studies, it can be observed that more than half of the patients have had drinking behavior within six hours before the injury in the violence-related trauma population [5,18,19]. As a psychomotor stimulant, drinking has been shown to increase aggressive behavior [20], whicht may be associated with a fact that the proportion of alcohol-related trauma caused by violence is always high, not only in this study, but also in previous studies [5,[10][11][12]. In the current study,24.89% of trauma involving alcohol resulted from tra c accidents, this was higher than the 4.8% reported by Kool [5] and 16% by Humphrey [21] and lower than the 47.4% by Nweze [11] and 44.7% by Browne [9].…”
Section: Discussionsupporting
confidence: 65%
“…In these published studies, it can be observed that more than half of the patients have had drinking behavior within six hours before the injury in the violence-related trauma population [5,18,19]. As a psychomotor stimulant, drinking has been shown to increase aggressive behavior [20], whicht may be associated with a fact that the proportion of alcohol-related trauma caused by violence is always high, not only in this study, but also in previous studies [5,[10][11][12]. In the current study,24.89% of trauma involving alcohol resulted from tra c accidents, this was higher than the 4.8% reported by Kool [5] and 16% by Humphrey [21] and lower than the 47.4% by Nweze [11] and 44.7% by Browne [9].…”
Section: Discussionsupporting
confidence: 65%
“…In these published studies, it can be observed that more than half of the patients have had drinking behavior within six hours before the injury in the violence-related trauma population [5,18,19]. As a psychomotor stimulant, drinking has been shown to increase aggressive behavior [20], whicht may be associated with a fact that the proportion of alcohol-related trauma caused by violence is always high, not only in this study, but also in previous studies [5,[10][11][12]. In the current study,24.89% of trauma involving alcohol resulted from tra c accidents, this was higher than the 4.8% reported by Kool [5] and 16% by…”
Section: Discussionsupporting
confidence: 65%
“…The mean age of participant was 38 years old, which is generally higher than previous studies [5,[9][10][11][12], which may be due to differences in inclusion and exclusion criteria. This study have found that the proportion of male population in alcohol-related trauma is signi cantly higher than that of female population, which is consistent with the published literatures [5,9,[12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 59%